Peranan yang dimainkan oleh Lembaga Kebudayaan Sabah (LKS) dalam mempromosikan dan memperkembangkan tarian Tradisional Sumazau Di Malaysia - Heanz Hemelton, bin Jaiti. (Universiti Malaysia Sarawak (UNIMAS), 2006)
Overall of this research is to assess the role and how the Lembaga Kebudayaan Sabah (LKS) to promote and envolve the Sumazau traditional dance in Malaysia. In this research the researcher want to assess how and what type of promotion that LKS takes to envolve the Sumazau traditional dance in Malaysia.